Non-lethal multiple pterygium syndrome (Escobar syndrome) with bilateral radial club hands: A case report - Gurung, Yam Prakash; Sharma, Sandeep; Banskota, Bibek; Rajbhandari, Tarun; Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2024)
Escobar Syndrome, the non-lethal variant of multiple pterygium syndrome (MPS), is a rare disorder. It is a subgroup of arthrogryposis multiplex congenita characterized by multiple webbing, fixed joint contractures, and distinctive facies like antimongoloid eyes, ptosis, micrognathia, low-set ears, high-arched palate, down-turned corners of lips, epicanthal folds, and long philtrum. Radial club hand is an uncommon congenital anomaly, and there is a loss of position on the radial aspect of the wrist because of the absence of the radius. This case has a very rare association between Escobar syndrome and bilateral radial club hands, and explores management strategies to improve function.